Travailler à la fabrique de l’information, ou comment l’imprévu devient une routine - Gaye Tuchman (Temporalités)
Noting that, on the one hand, variability in raw materials impedes routinization and that, on the other hand, organizations impose routines to control the flow of work, this article explores two related questions: (1) How can an organization routinely process unexpected events? (2) How do newsmen decrease the variability of events that form the raw material of news? The article examines five classifications used by newsmen to distinguish among events-as-news. First, the article analyzes these classifications as definitional “categories.” That approach failing for specified reasons, it views these same classifications as typifications. This analysis stresses the extent to which typification of raw materials arises out of the requirements of the organizational structure of news work. It pays special attention to some practical problems concerning the control of work. It also discusses the ramifications that arise for the news organizations from the manner in which an event occurs. Some implications of the analysis are discussed.